A signalling role for muscle glycogen in the regulation of pace during prolonged exercise - Rauch, H G L; St Clair Gibson, A; Lambert, E V; Noakes, T D (British journal of sports medicine, 2005)
Introduction: In this study we examined the pacing strategy and the end muscle glycogen contents in eight cyclists, once when they were carbohydrate loaded and once when they were non-loaded. Methods: Cyclists completed 2 hours of cycling at ∼73% of maximum oxygen consumption, which included five sprints at 100% of peak sustained power output every 20 minutes, followed immediately by a 1 hour time trial. Muscle biopsies were performed before and immediately after exercise, while blood samples were taken during the 2 hour steady state rides and immediately after exercise. Results: Carbohydrate loading improved mean power output during the 1 hour time trial (mean (SEM) 219 (17) v 233 (15) W; p<0.05) and enabled subjects to use significantly more muscle glycogen than during the trial following their normal diet. Significantly, the subjects, kept blind to all feedback except for time, started both time trials at similar workloads (∼30 W), but after 1 minute of cycling, the workload average 14 W higher throughout the loaded compared with the non-loaded time trial. There were no differences in subjects’ plasma glucose and lactate concentrations and heart rates in the carbohydrate loaded versus the non-loaded trial. Of the eight subjects, seven improved their time trial performance after carbohydrate loading. Finishing muscle glycogen concentrations in these seven subjects were remarkably similar in both trials (18 (3) v 20 (3) mmol/kg w/w), despite significantly different starting values and time trial performances (36.55 (1.47) v 38.14 (1.27) km/h; p<0.05). The intra-subject coefficient of variation (CV) for end glycogen content in these seven subjects was 10%, compared with an inter-subject CV of 43%. Conclusions: As seven subjects completed the time trials with the same end exercise muscle glycogen concentrations, diet induced changes in pacing strategies during the time trials in these subjects may have resulted from integrated feedback from the periphery, perhaps from glycogen content in exercising muscles.